Effects of Particle Size on the Shear Behavior of Coarse Grained Soils Reinforced with Geogrid - Kim, Daehyeon (Materials (Basel), 2014)
In order to design civil structures that are supported by soils, the shear strength parameters of soils are required. Due to the large particle size of coarse-grained soils, large direct shear tests should be performed. In this study, large direct shear tests on three types of coarse grained soils (4.5 mm, 7.9 mm, and 15.9 mm) were performed to evaluate the effects of particle size on the shear behavior of coarse grained soils with/without geogrid reinforcements. Based on the direct shear test results, it was found that, in the case of no-reinforcement, the larger the maximum particle size became, the larger the friction angle was. Compared with the no-reinforcement case, the cases reinforced with either soft geogrid or stiff geogrid have smaller friction angles. The cohesion of the soil reinforced with stiff geogrid was larger than that of the soil reinforced with soft geogrid. The difference in the shear strength occurs because the case with a stiff geogrid has more soil to geogrid contact area, leading to the reduction in interlocking between soil particles.